ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA PENGELOLAAN LIMBAH MEDIS PADAT DENGAN METODE JSA DI RSUD PASAR MINGGU TAHUN 2022 - Azarine Pandita Widyadhara (2022)
In 2021, it was recorded around 380.68 tons/day of solid medical waste in Indonesia, therefore waste management in health facilities is needed to minimize possible hazards. These waste management activities have various risks that can affect the safety and health of waste managers. This research aims to analyze the risks of occupational safety and health and determine the preventive control measures in the solid medical waste management process at Pasar Minggu Hospital. This type of research is qualitative with a descriptive study design. Data collection is done through observation; in-depth interviews with key informants and key informants; as well as airborne particle measurement and manual material handling. The risk analysis was carried out using the JSA method and referring to AS/NZS 4360. The results based on research showed that there were 8 possible risks classified into 4 potential hazards, namely, mechanical hazards, biological hazards, chemical hazards, and ergonomic hazards. Based on the risk assessment, three levels of risk are classified as high; one level of risk that is classified as moderate; and four levels of risk that are classified as low.